Integration of Social Emotional Learning (SEL) into Problem-Based Learning (PBL) to Improve Mathematical Representation - Monikasari, Chintya; Suryaningrum, Christine Wulandari; Sakdiyah, Halimatus (JURNAL PENDIDIKAN MATEMATIKA, 2025)
This classroom action research aims to improve students' mathematical representation abilities by applying problem-based learning (PBL) combined with social-emotional learning (SEL). PBL emphasizes problem-based learning, while social-emotional learning is a learning method that supports the development of students' social and emotional competencies. This study consists of two cycles, each containing steps, namely, planning, action, observation, and reflection. The instrument of this study uses a teaching module with the material of a two-variable linear inequality system. This study used subjects of class X 2 students of SMA Negeri 5 Jember in the 2024/2025 Academic Year. The results showed that applying PBL and social-emotional learning (SEL) can improve students' mathematical representation in verbal, visual, and symbolic aspects by 22.5%, from 70.6% to 93.1%. In addition, students' social-emotional competence (SEC) also increased by 21.7%, from 68.8% to 90.4%. Therefore, the integration of SEL in PBL can be an effective strategy for improving students' mathematical representation as well as social-emotional competence (SEC). Keywords: mathematical representation, PBL, SEL